Immunological Considerations for Improved Vaccines - Stacey, Hannah (My University, 2023)
Viral pathogens impose a significant burden on global public health. Given the increasing frequency of epidemics/pandemics, emphasis should be placed on improving current vaccines and developing next generation immunization strategies. The significant challenges observed in generating an efficacious seasonal influenza virus vaccine highlight the need for such advancements. Influenza results in approximately 650,000 deaths annually, most of which occur in pediatric, elderly, and immunocompromised patient populations. Currently approved influenza vaccines primarily elicit antibodies targeting the highly variable head domain of the hemagglutinin (HA) protein. Acquisition of point mutations in this region render antibodies elicited by seasonal vaccines less effective in subsequent seasons. Furthermore, seasonal vaccines do not provide protection from a pandemic influenza strain. Immense research efforts have, therefore, focused on the generation of a ‘universal’ influenza vaccine. Identifying optimal vaccine platforms is an ongoing challenge for influenza vaccine development. Vaccine delivery route and platform have been shown preferentially elicit different antibody isotypes. We demonstrated that stalk IgA antibodies elicit unique Fc-effector functions in neutrophils which may contribute to protection in vivo. As such, platforms which stimulate IgA should be considered for universal vaccines. Additionally, immune imprinting and pre-existing immunity to influenza impact both strain-specific and broadly-protective responses. In children, inactivated vaccines may skew immune responses to conserved regions of HA head shared by previously-encountered antigens. Induction of antibodies to conserved stalk epitopes is desired for a universal vaccine. We observed varied induction of stalk antibodies across vaccine platforms. Finally, seasonal vaccines can be of particular benefit to high-risk populations, such as patients with cardiovascular conditions, by preventing potentially life-threating exacerbations of their underlying conditions. We showed that inactivated seasonal vaccines were immunogenic and effective in these patients. These findings strengthen the observation that vaccine mediated protection helps to reduce cardiac events in vaccinated individuals. Together, this dissertation sheds light on factors affecting the elicitation and function of antibodies against influenza virus, which has implications for improving both seasonal and universal vaccine development. While the studies presented here focus on influenza virus, many of the findings may also be applied to other viral pathogens that cause respiratory infection, and are prone to antigenic drift, such as SARS-CoV-2.
Defining Features of Antibody- Mediated Immunity Against Influenza Virus: Implications for Optimal Vaccine Design and Delivery
Keywords: Influenza, viruses, vaccines, antibodies, Fc-effector functions, immune history, original antigenic sin